(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The article attempts to show various aspects of development of international law in relation to under-sea territories. A starting points is a concise analysis of circumstances accompanying the creation of the doctrine of continental shelf in the 50s. Then the author presents a gradual evolution of the development of law concerning under-sea territories, stressing that the process in a relatively short time exceeded a traditional outer bon-kr of continental shelf and comprised, in the 60s, the whole bottom of seas and oceans and not territorial waters only, as was the case in the 50s. A gradual evolution of the process which comprised territories of the bottom of oceans further and further away from the coast, including deep oceanic bottom, not coming within the state jurisdiction, resulted in complex regulation of legal situation of the whole bottom of seas and oceans in the convention on law of the sea adopted in 1982. The article discusses all basic solutions comprised in the convention and, in paritcular, the process of setting up norms demarcating outer border of continental shelf and consequences of having admitted deep oceanic bottom to be the "common heritage of mankind". In the article the process of development of international law concerning under-sea territories has been presented in view of interrelation of its particular stages, importance of various factors influencing the evolution of the above mentioned process and basic normative solutions defining present legal status of seas and oceans and their bottom.